The Civilian Conservation Corps in Alabama, 1933-1942 : a great and lasting good - Pasquill, Robert G. (UPCC book collections on Project MUSE., 2008)
The Civilian Conservation Corps was one of the better known and most successful of the New Deal programs following the Great Depression. The causes of the Great Depression have been addressed and debated from a variety of perspectives through the years. However, the effects explained in terms of human suffering leave little room for debate. By March of 1933, there were more than 13.6 million unemployed, and more than 200,000 of them were wandering the country looking for work. Homes and families were fractured. President Roosevelt proposed to put 500,000 unemployed men from cities and towns in.